Peningkatan Kemampuan Kepala Madrasah dalam Menyusun Rencana Kerja Madrasah melalui Pendampingan Manajerial secara Kolaboratif pada Madrasah Binaan Tahun 2024 - Sakdiah Sakdiah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Managerial mentoring in a collaborative manner is an effective strategy to improve the ability of Madrasah heads in preparing Madrasah Work Plans (RKM). This assistance is carried out through an approach based on cooperation, sharing, and discussion without being patronizing. Through this approach, Madrasah heads feel helped in carrying out their tasks, especially in preparing the RKM which is a reference for Madrasah management. The drafted RKM aims to: (1) achieve predetermined goals, (2) support coordination among stakeholders in Madrasah, (3) ensure consistency between planning, budgeting, implementation, and supervision, (4) optimize community participation, and (5) use resources efficiently, effectively, and sustainably. The results showed that the ability of Madrasah heads in preparing RKM had increased significantly after the assistance. In Cycle I, the average score of the RKM prepared was 74.70, increasing to 81.37 in Cycle II, with an increase of 8.93%. This finding shows that collaborative managerial assistance is effective in improving the competence of Madrasah heads in preparing quality RKM.